Talent Management dan Knowledge Management dalam Mempengaruhi Kinerja Karyawan di PT. Sari Fajar Waru Sidoarjo - Riko Bagus Prakoso; Sentot Imam Wahjono; Samsul Hadi; Marista Oktaviani (PROCEEDING UMSURABAYA, 2022)
The purpose of this study was to determine the simultaneous positive and significant effect of Talent Management and Knowledge Management on employee performance. This quantitative research approach uses hypothesis testing based on data obtained from distributing questionnaires. The population and sample in this study were 63 people. The results of this study indicate that there is a positive (0.397) and significant (0.000) influence between Talent Management and Employee Performance. The Knowledge Management variable has a positive (0.181) and essential (0.002) effect on employee performance. Lastly, Talent Management and Knowledge Management simultaneously have a positive (0.457) and practical (0.000) impact on Employee Performance.Keywords: Talent Management; Knowledge Management; Employee PerformanceÂ